2006
DOI: 10.1063/1.2174106
|View full text |Cite
|
Sign up to set email alerts
|

Transverse magnetic mode nonreciprocal propagation in an amplifying AlGaInAs∕InP optical waveguide isolator

Abstract: The design, fabrication, and characterization of an amplifying transverse magnetic ͑TM͒-mode optical waveguide isolator operating at a wavelength of 1300 nm are presented. The magneto-optical Kerr effect induces nonreciprocal modal absorption in a semiconductor optical amplifier with a laterally magnetized ferromagnetic metal contact. Current injection in the active structure compensates for the loss in the forward propagation direction. Monolithic integration of this optical isolator configuration with active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
55
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 9 publications
0
55
0
Order By: Relevance
“…The ellipticity is close to circular for the waveguiding mode. That is the reason why the experimentally observed transverse nMO effect in waveguides is substantial [9][10][11][12] . The data were calculated by solving Maxwell's equations and utilizing known optical and magneto-optical constants of transition metals 19,20 and semiconductors 21 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The ellipticity is close to circular for the waveguiding mode. That is the reason why the experimentally observed transverse nMO effect in waveguides is substantial [9][10][11][12] . The data were calculated by solving Maxwell's equations and utilizing known optical and magneto-optical constants of transition metals 19,20 and semiconductors 21 .…”
mentioning
confidence: 99%
“…The second example is light propagation in an optical waveguide covered by a ferromagnetic metal. In the case of a magnetic field applied perpendicularly to the light propagation direction in a waveguide plane, the absorption of the waveguide mode is significantly different for two opposite directions of the magnetic field [8][9][10][11][12] . The third example is a waveguide covered by a transparent MO material, in this case the propagation speed of waveguide mode changes when the applied magnetic field is reversed 13,14 .…”
mentioning
confidence: 99%
“…This modification occurs in both the real and imaginary part of k sp : k (1), the SPP modification under an applied magnetic field is nonreciprocal [k sp (B 0 ) = −k sp (B 0 )], thus making this kind of system very interesting for the design of integrated optical isolators, [22][23][24][25][26] another fundamental piece for the development of nanophotonic circuits. Another advantage of the magnetic field driven systems is related to its potential switching speed, as it has been recently demonstrated that materials magnetization switching is an ultrafast phenomenon that can achieve the terahertz regime.…”
Section: Introductionmentioning
confidence: 99%
“…Garnets, with their unique magneto-optical (MO) properties have been the material of choice for building passive non-reciprocal devices [7][8][9][10] . In general, non-garnet non-reciprocal devices are active devices that require external power sources, which increase the complexity and cost of the device [11][12][13][14] . MO effects in garnets are the result of non-zero off-diagonal components in the dielectric matrix (ε) which break time-reversal symmetry.…”
Section: Abstract: Abstract: Abstractmentioning
confidence: 99%